PERBEDAAN EFEKTIVITAS SELF MYOFASCIAL RELEASE DENGAN LATIHAN PENGUATAN TERHADAP NYERI DAN KNEE PERFORMNCE PADA ILIOTIBIAL BAND SYNDROME (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2017)
AbstractObjective : To determine difference effect of self myofascial release with strengthening exercises on pain and knee performance of iliotibial band syndrome. Methods : research quasi experimental. Sample of 14 people in the Esa Unggul University, choosen by purposive sampling. Results : Normality test using shapiro wilk test and homogenity test using levene’s test. Hypothesis test I using paired sample t-test, p= 0,001 for VAS average after 32,14±11,495 and p=0,001 for speed run average after 5,06±0,336 which means self myofascial release effective in reducing pain and increase knee performance. In the treatment group II with paired sample t-test , p=0,001 for VAS average after 19,29±9,322 and p=0,001 for speed run average after 4,48±0,4888 which means strengthening exercises effective reduce pain and increase knee performance. Result of independent sample t-test for VAS average after I (32,14±11,495) p=0,040 and II (19,29±9,322 ) and for speed run average after I (5,06±0,336) and II (4,48±0,4888) p=0,024 which means there are differences effect self myofascial release with strengthening exercise to pain and knee performance on iliotibial band syndrome. Conclusion : There is a difference in effectiveness between self myofascial release with s`trengthening exercise towards reduction pain and increased knee performance of iliotibial band syndrome. Keywords : Self myofascial release, strengthening exercise, Iiiotibial band syndrome  AbstrakTujuan : untuk mengetahui perbedaan efektivitas antara self myofascial release dengan latihan penguatan terhadap nyeri dan knee performance pada iliotibial band syndrome. Metode : penelitian quasi exsperimental. Terdiri dari 14 sampel di lingkungan Universitas Esa Unggul, tekniknya purposive sampling. Hasil : Uji normalitas menggunakan Shapiro Wilk Test dan uji homogenitas mengguakan Levene’s Test. Uji hipotesis I dengan paired sample t-test, didapatkan nilai p=0,001 untuk VAS dengan rerata sesudah 32,14±11,495 dan p=0,001 untuk kecepatan lari dengan rerata sesudah 5,06±0,336 yang berarti self myofascial release dapat menurunkan nyeri dan meningkatkan knee performance. Pada kelompok perlakuan II dengan paired sampel t-test, didapatkan nilai p=0,001 untuk VAS dengan rerata sesudah 19,29±9,322 dan p=0,001 untuk kecepatan lari rerata sesudah 4,48±0,4888 berarti latihan penguatan dapat menurunkan nyeri dan meningkatkan knee performance. Pada hasil independent sample t-test . VAS rerata sesudah I (32,14±11,495) dan II (19,29±9,322) maka p=0,040 dan kecepatan lari rerata sesudah I (5,06±0,336) dan II (4,48±0,488) maka p=0,024 untuk kecepatan lari berarti ada perbedaan efek self myofascial release dengan latihan penguatan terhadap nyeri dan knee performance pada iliotibial band syndrome. Kesimpulan : ada perbedaan efektifitas antara self myofascial release dengan latihan penguatan terhadap penurunan nyeri dan peningkatan knee performance pada iliotibial band syndrome. Kata kunci : Self myofascial release, latihan penguatan, iliotibial band syndrome